Stochastic properties and pricing of bitcoin using a GJR-GARCH model with conditional skewness and kurtosis components - Theodossiou, Panayiotis; Ellina, Polina; Savva, Christos S. (My University, 2022)
Using a flexible statistical framework that accounts for time-varying skewness and leptokurtosis, we examine the stochastic behavior of Bitcoin in comparison to five major currencies. The empirical findings reveal that the distribution of all series is leptokurtic. Once the effect of skewness-kurtosis is considered, the true price of risk is obtained, with implications on policymakers’ and investors’ strategies.
Keywords: Conditional skewness and kurtosis; Skewness price of risk; Upside and downside market probabilities; Skewed generalized error distribution